ETHNOLINGUISTIC INSIGHTS INTO MINANGKABAU CULINARY TRADITIONS: INTEGRATING CULTURAL AND LINGUISTIC PERSPECTIVES ON RENDANG APPRECIATION IN EDUCATIONAL CONTEXTS - Rahayu, Rahayu; Syifaurrohmah, Syifaurrohmah; Aryanto, Bagya (INOVISH JOURNAL, 2024)
The Minangkabau community, hailing from West Sumatra, Indonesia, holds deep-rooted cultural values that permeate their culinary practices. Rendang, a slow-cooked meat dish with rich, complex flavors, serves as a quintessential example of their gastronomic heritage. Ethnolinguistic analysis unveils the intricate relationship between language, culture, and food in Minangkabau society. This study offers an unique lens through which to explore the culinary traditions of the Minangkabau people, particularly in the context of appreciating dishes like rendang. This abstract aims to integrate both cultural and linguistic perspectives into educational contexts. Linguistic exploration reveals that the names of traditional dishes often carry layers of cultural significance. In the case of rendang, linguistic nuances reflect not only the ingredients and cooking process but also historical narratives, social structures, and religious influences. Understanding these linguistic subtleties is crucial for a comprehensive appreciation of Minangkabau cuisine. Moreover, ethnolinguistic studies shed light on the role of language in preserving culinary knowledge and transmitting cultural values across generations. In educational contexts, incorporating ethnolinguistic perspectives into the study of Minangkabau culinary traditions can enrich cross-cultural understanding and promote intercultural competence. By exploring rendang appreciation through a cultural and linguistic lens, educators can engage students in meaningful discussions about food as a manifestation of identity, history, and social dynamics. In conclusion, ethnolinguistic insights offer a holistic framework for exploring Minangkabau culinary traditions, particularly the appreciation of rendang as one of the  world's most delicious dish. Integrating cultural and linguistic perspectives into educational contexts not only enhances culinary literacy but also fosters a deeper appreciation for the cultural richness and diversity of Indonesia and beyond.